Exogenous pyruvate represses histone gene expression and inhibits cancer cell proliferation via the NAMPT–NAD+–SIRT1 pathway. Issue 21 (10th October 2019) - Ma, Rui; Wu, Yinsheng; Zhai, Yansheng; Hu, Bicheng; Ma, Wei; Yang, Wenqiang; Yu, Qi; Chen, Zhen; Workman, Jerry L; Yu, Xilan; Li, Shanshan
Abstract: Pyruvate is a glycolytic metabolite used for energy production and macromolecule biosynthesis. However, little is known about its functions in tumorigenesis. Here, we report that exogenous pyruvate inhibits the proliferation of different types of cancer cells. This inhibitory effect of pyruvate on cell growth is primarily attributed to its function as a signal molecule to repress histone gene expression, which leads to less compact chromatin and misregulation of genome-wide gene expression. Pyruvate represses histone gene expression by inducing the expression of NAD + biosynthesis enzyme, nicotinamide phosphoribosyltransferase (NAMPT) via myocyte enhancer factor 2C (MEF2C), which then increases NAD + levels and activates the histone deacetylase activity of SIRT1. Chromatin immunoprecipitation analysis indicates that pyruvate enhances SIRT1 binding at histone gene promoters where it reduces histone acetylation. Although pyruvate delays cell entry into S phase, pyruvate represses histone gene expression independent of cell cycle progression. Moreover, we find that administration of pyruvate reduces histone expression and retards tumor growth in xenograft mice without significant side effects. Using tissues from cervical and lung cancer patients, we find intracellular pyruvate concentrations inversely correlate with histone protein levels. Together, we uncover a previously unknown function of pyruvate in regulating histone gene expression and cancer cell proliferation.